The role of ijtihad in determining the provisions of contemporary transactions - Abd Halim, Muhammad Silahuddin; Shahabuddin, Muhammad Syakib Najmii; Mohd Zamashary, Muhammad Hariz; Mohd Amin, Muhammad Amir Azfar; Kamanedin, Kamarulhariz Akmal (2024)
In Islamic jurisprudence, ijtihad, derived from the Arabic root j-h-d (effort or exertion of effort), is one of the most profound legal and intellectual traditions. In the absence of explicit precedents, this method of independent reasoning is used by qualified scholars to derive legal rules from the Quran and Sunnah, the two pillars of Islam in the past. This technique has been an essential tool for dealing with new problems and adapting Islamic law to suit current circumstances. The Qur'an and the sayings and actions of the Prophet Muhammad (peace be upon him) were directly consulted by the early Islamic community. However, as the Islamic entity grew, embraced multiple cultures, and faced unprecedented social, economic, and political challenges, jurists realized that a systematic framework was required to derive rulings for cases not specifically addressed in the primary writings. Ijtihad reached its peak during the classical era and was practiced in the early stages of Islamic jurisprudence. Ijtihad was used in the methods of prominent scholars such as Ahmad ibn Hanbal, al-Shafi'i, Abu Hanifa, and Malik ibn Anas. This process facilitated the development of several schools of thought (madhahib), each offering complex interpretations of Islamic law. The foundation of the development of jurisprudence is ijtihad, which ensures that Islamic legal ideas are always adaptable and progressive. It bridges the gap between divine commandments and human reality through critical interpretation and analysis, and rigorous intellectual discipline. Adherence to accepted jurisprudential principles and the ethical need to maintain justice are its guiding principles.